Analisis Validitas Menggunakan Model Rasch Dalam Pengembangan Instrumen Uji Konsep Alkana - Sri Mulyanti; Suwahono Suwahono; Hanifah Setiowati; Lis Setiyo Ningrum (Postgraduate, University of Mataram, 2022)
This study aims to test the feasibility of the test instrument as a measuring tool for student knowledge of alkane compounds in the online form of 15 multiple choice questions on the concept of characteristics, physical properties, and nomenclature of alkanes. The questions were tested on 85 students who had studied the subject of alkanes. The feasibility analysis includes the level of problem difficulty, construct validity, content validity, and reliability. The results of the analysis show that the items developed are feasible according to the Rasch model.